LET'S START YOUR OWN VLOG PROMOTING INDONESIAN DIGITAL ENTREPRENEUR USING YOUTUBE CHANNEL - Sujoko, Anang; Fatanti, Megasari N. (Jurnal Aplikasi Manajemen, 2017)
This research uses interpretive approach through visual semiotics method. Visual semiotics method is done by purposive sampling the most popular five videos that have been produced and uploaded by Bayu SKAK on his YouTube channel. The researcher also gathers some data from second resources to find out its impact on economic site. The result of the research shows that YouTube as a public communication channel and entrepreneurship. Bayu SKAK's video blogging consists of creative ideas and also a media for digital entrepreneurship. Digital entrepreneurship is able to create a new environment for evolutionary creative industries that are based on ideas, networking, and self-creativity. The culture and communication pattern is developed between the Vlogger as the creative producer and the audience as the consumer of vlogs. On one side, YouTube channels have been an open commercial public space for people of the age of information, has more than one role by being the audio-visual consumer and also the producer, on the other side there have been problems, such as institutional problems, copyright protection, and advertisement management. However, socializing the use of video blogging through YouTube channels can be an alternative way to improve and develop digital entrepreneurship in Indonesia. Educating the society through social media can promote the various types of new businesses based on digital entrepreneurship through the creativity and the contribution of teenagers to digital native. This research does not reveal the Vlogger's strategy to attract large viewers, and it becomes an important issue to explore the benefits of social media.